Perancangan Sistem Informasi Pengelolaan Gudang Pada PT Sanjaya Amar Persada Sawangan Berbasis Web - Bayu Apriansyah Santoso; Thoyyibah T. (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Warehouse management in a company is certainly very important so that all goods in the warehouse are well organized. The development of the company in all fields is currently growing very rapidly, therefore the company is required toexpand its business by implementing a system in the inventory warehouse. PT. Sanjaya Amar Persada Sawangan is engaged in providing Technical Supports ervices that support the program of effectiveness and functional optimization of banking equipment. While the warehouse management systema tPT. Sanjaya Amar Persada Sawangan is still conventional, so a warehouse management information system is needed. The warehouse management information system is made web-based and is carried out using the Rapid Application Development (RAD) methodwhich is a linear sequential software development model that emphasizes a shortdevelopment cycle. The data mining method used is observation and literaturestudy. The programming used is website programming using MySQL and PHP databases. In the warehouse management information system is suspected to beable to help the warehouse staff of PT. Sanjaya Amar Persada Sawangan inmanaging stock of goods, searching for goods data and making reports. With theimplementation of this system, it is expected to reduce errors that may occur in thewarehouse of PT. Sanjaya Amar Persada Sawangan.